Galvanic replacement reaction in perovskite oxide for superior chemiresistors. Issue 43 (24th October 2022) - Baek, Jong Won; Kim, Yoon Hwa; Ahn, Jaewan; Kim, Dong-Ha; Shin, Hamin; Ko, Jaehyun; Park, Seyeon; Park, Chungseong; Shin, Euichul; Jang, Ji-Soo; Kim, Il-Doo
Abstract : This work presents the synthesis of LaFeO3 /SnO2 nanotubes (NTs) based on the GRR process, with perovskite LaFeO3 NTs prepared by electrospun nanofibers as the starting material resulting in a significantly enhanced catalytic activity. Abstract : It is well known that certain gas molecules can serve as specific markers for characterizing the physiological and environmental nature of a subject, such as acetylene gas which can be used for determining a person's smoking status as well as for monitoring air pollution levels. For their reliable detection, gas sensors should be designed with high sensing capabilities in terms of selectivity, sensitivity and low detection limit. In this work, we present a rational design approach for the synthesis of p-type LaFeO3 /n-type SnO2 composite nanotubes (NTs) via galvanic replacement reaction (GRR) on electrospun perovskite LaFeO3 NTs for p–n type-converted sensing. The GRR process provides LaFeO3 /SnO2 NTs with high surface area (146.6 m 2 g −1 ) by generating SnO2 nanograins (<10 nm), as controlled by varying the reaction time. The abundant heterogeneous p–n junctions formed in LaFeO3 /SnO2 NTs contribute to the dramatic improvements in their sensing characteristics. In fact, the LaFeO3 /SnO2 NTs exhibited 31.2-fold increased response toward acetylene (5 ppm) with a far improved response speed (16 s) compared to that of pristine LaFeO3 NTs (64 s). Our results demonstrate that the GRR process can be used to engineer the morphology and composition of p-type perovskites to achieve exceptional chemical sensing performances.